Legitimacy of business ethics across cultures - Mah, Sherwin Liang Yung (2008)
This paper discusses whether the uniqueness of culture will pose a problem in the universality of business ethics. Attempts were made to show that cultures are indeed unique and our findings point towards cultural groupings similar to the TRIAD. The paper conclude with an analysis of the possible implications on businesses and other related parties.